La justicia indígena y sus conflictos de competencia con la justicia ordinaria, comunidad Tagma San José, cantón Guaranda, Provincia Bolívar. - Manobanda Chimbo, Oscar Edison (2024)
The research topic: Ecuador is an Intercultural and Plurinational State (Art. 1 C R E) whose administration of justice is characterized by the confluence of two different administrations of justice, applied by different bodies, in different jurisdictions and with a normative basis that could be totally opposed. This legal pluralism is composed of the ordinary justice administration system structured by the different jurisdictional bodies and the administration of indigenous justice based on the line of customs and traditions unique to each community, which also represents an important part of their identity that has been preserved over the years. In Ecuador, legislation has not been developed in a coherent manner to properly harmonize the indigenous administration system with the ordinary justice administration system, despite the principles emanating from the Constitution itself. Another important element is the lack of coercive force so that the existing regulations can be applied, since there are many cases in which the administration of indigenous justice has exceeded its powers and in the same sense the ordinary administration has not been able to fully harmonize with the indigenous justice system. It is important to consider that speaking of the ordinary justice system we are governed by a written system whose force of application lies in the rules of natural law, this apparent rigidity has been one of the main reasons why it has not been possible to adapt and understand the principles and bases governing indigenous justice. The present investigation is justified, since it is a topic of social, normative and legal interest of great relevance for the country, which will contribute with legal knowledge for the population in general; knowledge that can be built with the help of a legal, doctrinal and customary analysis, attending to the principles, traditions and customs of the Tagma San José community, by means of which the Constitutional right of autonomy for this community is sought to be made effective. The present research was developed under a qualitative approach, using the inductive, historical and analytical methods of investigation, which allowed gathering and analyzing information regarding the ways in which justice is administered within this community and the conflicts of competence that may arise in this community. As expected results, it is expected to better elucidate the existence of conflicts between ordinary justice and indigenous justice within the Tagma San José community, and if so, to determine which is the level of conflict, in order to develop mechanisms to solve these conflicts that may arise in the future. 5 Key words: Indigenous community, conflicts of competence, resolutions, community assembly, cabildo, versus, Sumak Kawsay, Ayllu.